E-Participation: Community Involvement Level Related to Different Services of Local Government Unit Officials - Balahadia, Francis F; Molino, Wellanie M; Bawica, Joel M; Juanatas, Irish C; Balmeo, Henry Dyke; Ballera, Melvin A (International Journal of Computing Sciences Research, 2017)
Purpose – This paper seeks to answer the level and extent of involvement of the community in the government services to explore how information technologies may work to improve the services to the citizens as an input to e-governance initiative. Method –The researchers conducted a series of activities for data gathering, such as interview, focus group discussion and survey. Questionnaires were used to collect data to support the rationality of the study. The study used the descriptive statistics from the gathered data to determine the needs of the community. Specifically, mean scores and standard deviation were computed from the results of different statements per category based on the survey questions. Regression analysis method was used to identify the factors affecting the involvement of the respondents related to the services from the LGU. ANOVA was also used to identify the differences among respondents’ levels of involvement such as the age group, civil status, and educational attainment. Results – The findings provided justifications to identify factors affecting the involvement of the respondents in LGU services. It also indicated that they have the same level of involvement in terms of sex, civil status, and educational attainment. However, there is a positive association between community involvement and community respondent age group in terms of involvement level. Conclusion – The study showed that there is lack of information dissemination about different services, programs, activities and projects in the community that cause low community involvement. Accessibility to technology of the respondents, dissemination of information to respondents through the web, level of public web applicability of the respondents, and level of assessment on incident report in the community of the respondents are the factors affecting the involvement of the respondents in the different services of local government officials which lead as a basis for creating the e-participation website for local government unit. Recommendations – The use of ICT (information and communication technology) in the Local Government must be applied in a bigger community or group in a barangay; on the other hand, local municipalities must implement the proposed system or e-participation portal to identify the benefits from the delivery of services of the officials. Research Implications – The development of the government services such as e-participation initiatives inevitably need to take into consideration the inclusion of proper information dissemination, crafting of new models of policy formulation, and the formulation of alternative approaches for connecting people to the political process though the ICT. Motivations for community involvement are also important. Future efforts could stress on the community their involvement in changing the local conditions they are not pleased with. Uses of this finding in program/policy development could take a variety of forms.